Exploring the Role of Grandparenting in Enhancing the Positive Mental Health of Children from External Migrant Worker Families - Azam Syukur Rahmatullah; Kamsih Astuti; Idi Warsah; Suyatno Suyatno; Jaenullah Jaenullah (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung in collaboration with Asosiasi Bimbingan dan Konseling Indonesia (ABKIN), 2023)
The rising number of Indonesian migrant workers has led to many children being left in the care of their grandparents, who may lack parenting knowledge and cause confusion, affecting the children's personalities. This research focuses on strengthening the positive mental health of migrant workers’ children by their grandmothers as their caregivers in PuringKebumen District, Central Java, Indonesia, selected based on research criteria. The seven Muslim grandmothers produced parenting products with positive mental health demonstrating healthy character, personality, and behavior. The research belongs to field research with a phenomenological approach, while the data collection methods implemented were observation and interviews. This study had four technical criteria for checking data validity: credibility, dependability, transferability, and confirmability. The data obtained were then analyzed reductively, phenomenologically, and editically during data collection. The method of data analysis was done by reducing data, presenting data, drawing conclusions, and carrying out data verification. The results showed that the seven grandmothers focused on strengthening the positive mental health of their grandchildren because a positive mentality could shape positive character, behavior, temperament, and manners, which is the primary source of human beings. Apart from that, the grandchildren become noble individuals wherever they are, get recognition from others because of the good they have done, and be able to reassure their hearts. The basic principles used in the parenting process to strengthen the positive mental health of their grandchildren included trust, strengthening religion-spiritual, honesty, unconditional love, sincerity, steadfastness, earnestness, consistency, and teaching and developing morals in upbringing.